Cycle Related Mean Square Cordial Graphs - Murugam, Dr. A. Nellai; Heerajohn, S. (IJRDO -JOURNAL OF MATHEMATICS, 2015)
Let G = (V,E) be a graph with p vertices and q edges. A Mean Square Cordial Labeling of a Graph G with vertex set V is a bijection from V to 0, 1 such that each edge uv is assigned the label ( ⌈(